Investigating Post Merger Synergy and Integration of Sapura – Kencana A Case Study - Anwar, Edzwan Redza (2015)
Merger and Acquisition (M&A) was the result of many contributing factors in any organization namely,corporate growth (Shrivastava, 1988), corporate strategy (School, 1987), diversification and renewal(Nahavandi & Malekzadeh, 1988), strategic alliances (Doz & Hamel, 1998), respond to financial markets (Häkkinen, 2005), all led by value creation goal. Companies see M&A as means to pursue their long term strategic goals (Gaughan, 2010). The goal is paved from strategic vision rational to create long term competitive advantage, sustainable and profitable business. Post Merger Integration means not only merging of business activities and formal structures towards economic success, but also tackling sociocultural and organizational aspects (Maire & Collerette, 2011). Completion of contract signing is only a part of the overall M&A exercise. Merger involves fundamental changes in administrative and structure,and the greater the merger, it will require more complex intervention to help manage the integration. Otherwise, it will impede the merger performance and potential benefits and synergies. The real issues and challenges in PMI arise when merged organization tries to work together as one. Organizations seize to secure the effective and efficient management team to organize its combined resources and achieve common goals. Based on this understanding, the author would like to analyse outcome of Sapura‐Kencana M&A using the 6S Watchlist Framework. This research has been set out analyze the value creation from the merger of and revealing its success factors by analyzing and investigating the degree of integration and the decision made during PMI and discovering the underlying drivers SK merger and its causes. The author has undertaken specific task to analyze the degree of integration, and investigate the decision made in pre,present, and post‐merger in SK. The author examines the effects of the merger from the 6S Watch List Framework which 1)Strategy, 2)Social and Cultural, 3)Structure (Organization/Integration Team), 4)Speed, 5)Success (Technological Knowledge), and 6)Surrounding (Environment/Communication), and concluded the findings in the Conclusion section.